Interior Architecture Design for Alex’s Salon - Mellisa Christy Suhendro; Freddy Handoko Istanto; Maureen Nuradhi (Universitas Ciputra Surabaya, 2015)
Population growth in the developing city led to increased business development one significant property business and have an impact on the interior business. Lifestyle is more developed and modern influence to the needs and demands of society. Increased property business and restaurant make people competing to be the best, one of the strategies are attracting consumers through interior design offered. Therefore, Kretyv Interior Consultants has a big oppurtunities as an interior consultant here that provide appropriate solutions to problems and consumer demand good quality work. Kretyv Interior Consultant will focus on residential projects because the number of residential and hospitality will increase each year. One way to reach customers is to renovate Alex’s Salon. Be expected, Kretyv can be known by public.